ANALYSIS TOTAL HARDNESS WATER WELL IN VILLAGE KEDUNGREJO PURWODADI GROBOGAN DISTRICT WITH COMPLEXOMETRY METHOD - Raligia Dewandi Susilo; R. Taufiq Nur Muftiyanto; Waskitho . (STIKES DUTAGAMA KLATEN, 2017)
Background: The problem that is often seen in water services that the quality of ground water is less qualified as potable water. One of the chemical parameters in water quality requirements is the total of element content of Ca 2+ and Mg 2+ in the presence of water commonly called water hardness. Hardness in water no demand either for domestic use or for industrial use, the maximum levels allowed CaCO3 hardness is 500 mg / L. Most people do not understand about the adverse effects of hard water consumption and processing method was still not right. Objective: This study aimed to determine the extent of the total hardness of water wells in the village Kedungrejo Purwodadi Grobogan district. Method: complexometry titration method. Results: From this analysis obtained total hardness levels ranging from 62.39 - 419.40 mg CaCO3 / L. Conclusion: The level of water wells in the village Kedungrejo Purwodadi including the high classification, seasonal factors also affect the size of the sample when tested. Lack of public awareness of the importance of fresh water consumed and increased use soap.